Transactions on Rough Sets XVI - Peters, James F.; Skowron, Andrzej; Ramanna, Sheela; Suraj, Zbigniew; Wang, Xin.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The LNCS journal Transactions on Rough Sets is devoted to the entire spectrum of rough sets related issues, from logical and mathematical foundations, through all aspects of rough set theory and its applications, such as data mining, knowledge discovery, and intelligent information processing, to relations between rough sets and other approaches to uncertainty, vagueness, and incompleteness, such as fuzzy sets and theory of evidence. Volume XVI includes extensions of papers from the Rough Sets and Knowledge Technology Conference which was held in Banff, Canada, in October 2011. In addition this book contains a long paper based on a PhD thesis. The papers cover both theory and applications of rough, fuzzy and near sets. They offer a continuation of a number of research streams which have grown out of the seminal work by Zdzislaw Pawlak during the first decade of the 21st century.
Generalized Probabilistic Approximations -- An Extension to Rough c-Means Clustering Algorithm Based on Boundary Area Elements Discrimination -- Granular Computing: Topological and Categorical Aspects of Near and Rough Set Approaches to Granulation of Knowledge -- The Concept of Reducts in Pawlak Three-Step Rough Set Analysis -- Nearness of Subtly Different Digital Images -- Semantic Clustering of Scientific Articles Using Explicit Semantic Analysis -- Maximal Clique Enumeration in Finding Near Neighbourhoods -- On Fuzzy Topological Structures of Rough Fuzzy Sets -- Approximation of Sets Based on Partial Covering.
Keywords: Computer science; Electronic data processing; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Pattern Recognition; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Numeric Computing; Image Processing and Computer Vision